Analisis Desentralisasi Fiskal terhadap Belanja Modal Pemerintah Daerah di Indonesia - Hady Sutjipto; Stania Cahaya Suci; Yogi Sabarudin Umbara (Politeknik Keuangan Negara STAN, 2019)
The aims of this study to determine the effect of the degree of fiscal autonomy, regional financial dependence, and population on capital expenditure of 34 provinces in Indonesia. The Methodolody in this study employs panel data analysis method with fixed effect model (FEM) estimation model. Determination of samples based on panel data consisting of time series data for period 2014-2017 and cross section data of 34 Provinces in Indonesia. The data was obtained from the Central Statistics Agency and the Directorate General of Financial Balance.The results shows that (1) the degree of fiscal autonomy, regional financial dependence, and the population have a positive and significant effect on capital expenditure (2) the degree of fiscal autonomy, regional financial dependence, and the total population have simultaneous effect on capital expenditures.